2011
DOI: 10.1007/s00449-011-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic liquids on enzymatic synthesis of caffeic acid phenethyl ester

Abstract: Although caffeic acid phenethyl ester (CAPE), an active flavonoid, plays an important role in the antioxidant activity of honeybee propolis, the isolation of CAPE from honeybee propolis is time-consuming due to wide variety of impurities present. Therefore, biochemical method to synthesize CAPE was investigated in this study. Since ionic liquids (ILs) possess some unique characteristics as appreciated alternatives to conventional solvents for certain biotransformation, the effect of ILs as reaction media for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Figure 6 B shows the effect of reaction temperature on the yield of CAPE in the biphasic system; an increase in the reaction temperature during the range of 65–75 °C led to an increase of the total CAPE yield until 60 h. This indicated that the increasing of temperature might improve the solubility of MC in [Bmim][Tf 2 N], reduce IL viscosity and decrease mass transfer limitations [ 8 , 11 ]; also, this could strengthen the solubility of CAPE in solvents, accelerate the complexation reaction and promote the equilibrium of complex formation with TOPO. However, with a temperature higher than 75 °C, the total yield notably decreased, most likely due to partial damage on the complex formations between CAPE and TOPO and thermal inactivation of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 B shows the effect of reaction temperature on the yield of CAPE in the biphasic system; an increase in the reaction temperature during the range of 65–75 °C led to an increase of the total CAPE yield until 60 h. This indicated that the increasing of temperature might improve the solubility of MC in [Bmim][Tf 2 N], reduce IL viscosity and decrease mass transfer limitations [ 8 , 11 ]; also, this could strengthen the solubility of CAPE in solvents, accelerate the complexation reaction and promote the equilibrium of complex formation with TOPO. However, with a temperature higher than 75 °C, the total yield notably decreased, most likely due to partial damage on the complex formations between CAPE and TOPO and thermal inactivation of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…However, an aqueous/organic system is not suitable for water-sensitive lipase-catalyzed reactions. Recently, ionic liquids (ILs) have been applied as solvents in lipase-catalyzed reactions to synthetize a myriad of products [ 8 , 9 , 10 ]. It is widely believed that lipases in ILs possess higher activity, stability and selectivity, which can increase the yield of products and the conversion of feedstocks [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A própolis chinesa também é rica em flavonoides e em ácidos fenólicos, sendo que alguns tipos apresentam maior atividade porque possuem em sua composição os ácidos caféico, ferúlico e CAPE (CHEN et al, 2003;AHN et al, 2007;HA, et al, 2012). De acordo com a literatura, a própolis chinesa, argentina e europeia possuem os flavonoides crisina e galangina em grande concentração, os quais são considerados os mais ativos do ponto de vista antioxidante (GARDANA et al, 2007;MOREIRA et al, 2011).…”
Section: Própolis E Sua Composição Químicaunclassified
“…Por otro lado, la esterificación de AC y 2-FE catalizada con Novozym® 435 se ha llevado a cabo con altas conversiones y rendimientos (92-100%). Sin embargo, para obtener estos resultados se requiere de una gran cantidad de catalizador (15-17.8 mg de biocatalizador/mg AC) (Widjaja et al, 2008;Chen et al, 2010;Ha et al, 2012). Esto probablemente se debe a la baja afinidad del biocatalizador por el sustrato.…”
Section: Revisión Bibliográficaunclassified